The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1159/000233883
|View full text |Cite
|
Sign up to set email alerts
|

Hyperventilation-Induced Bronchoconstriction in Guinea Pigs

Abstract: The purpose of this study was to investigate the pulmonary effects of hyperventilation in anesthetized, mechanically ventilated guinea pigs. Airway resistance (Raw), dynamic lung compliance (CDyn), blood pressure (BP), heart rate (HR), arterial blood gases (PaO2, PaCO2), pH and arterial plasma HCO3–– were measured before and after a 10-min period of hyperventilation produced by increasing the respiratory rate from 60 to 120 breaths/min while maintaining ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Hyperventilation with dry air increases airway resistance in guinea pigs (1), rabbits (2), cats (3), dogs (4), monkeys (5), and humans (6). Other studies reveal that it damages the bronchial mucosa (7,8), increases bronchial blood flow (9,10), and increases bronchovascular permeability (8, 1 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperventilation with dry air increases airway resistance in guinea pigs (1), rabbits (2), cats (3), dogs (4), monkeys (5), and humans (6). Other studies reveal that it damages the bronchial mucosa (7,8), increases bronchial blood flow (9,10), and increases bronchovascular permeability (8, 1 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that NK-receptor antagonists do not abolish AIB in guinea-pigs [69] suggests that other mediators or mechanisms account for the residual component in this model. The magnitude of AIB (measured as an increase over baseline resistance) elicited from guinea-pigs hyperventilated with hyperoxic gas [6,15] tends to be markedly greater than that reported for either this species [7,52], or other species [8,9,12,13], hyperventilated with normoxic gas ( fig. 1).…”
Section: Calcium Antagonistsmentioning
confidence: 73%
“…Unless otherwise specified, all species were hyperventilated with either dry room air or 5% CO 2 and dry air. a) Guinea-pigs: hyperventilated with dry gas containing 95% O 2 ( ---❍ ---) (data from RAY et al [6]); hyperventilated with dry gas containing 21% O 2 ( ∆ ) (data from CHAPMAN and DANKO [7]). b) Rabbits: sensitized to ovalbumin ( ---❍ ---); nonsensitized ( ∆ ) (data from KOYAMA et al [8]).…”
mentioning
confidence: 99%
“…Hyperpnea of cold and/or dry air precipi tates bronchoconstriction in anesthetized guinea pigs [11][12][13][14][15], The bronchoconstrictor response probably involves endogenously re leased tachykinins because the bronchospasm is potentiated by treatment with NEP inhibi tors [6,7] and is attenuated by selective NK-1 and NK-2 receptor antagonists [8], Further more. hvpcrpnea-induced bronchospasm in guinea pigs is reduced in animals depleted of sensory neuropeptides with capsaicin treat ment [6].…”
Section: Discussionmentioning
confidence: 99%
“…RL and Coyn were mea sured immediately before the start o f the hyperventila tion period and again 10 min after the hyperventila tion was terminated. This time was selected because we have previously found that peak changes in Rj and CDyn occur within 10 min o f terminating hyperventila tion [11], Only one hyperventilation challenge was giv en to each animal.…”
Section: Bronchoconstriction Due To Hyperventilationmentioning
confidence: 99%